Effects of nitric oxide on chondrocyte migration, adhesion, and cytoskeletal assembly - Sally R. Frenkel; Robert M. Clancy; John L. Ricci; Paul E. Di Cesare; John Rediske; Steven B. Abramson (1996)
Abstract Objective . The migration of cells of chondrocyte lineage is believed to play a role in cartilage growth and repair. The present study examined 1) whether chondrocytes are capable of migration in vitro; and 2) the effects of nitric oxide (NO) on chondrocyte migration, adhesion, and cytoskeletal assembly. Methods . Chondrocyte migration was evaluated by 2 assays: 1) “centrifugal” migration within a 3‐dimensional collagen matrix (dot culture); and 2) directed migration under agarose in response to bone morphogenetic protein. To assess the effects of NO, chondrocytes were treated with either exogenous NO (S‐nitrosoglutathione [SNO‐GSH]) or a mixture of cytokines known to induce endogenous NO production. The effects of NO on chondrocyte adhesion to fibronectin‐coated surfaces, as well as on actin polymerization (determined by indirect immunofluorescence), were also examined. Results . The capacity of chondrocytes to migrate was demonstrated both by the dot culture and by agarose methods. Both SNO‐GSH and endogenous NO induced by cytokines inhibited this migration. Exposure to NO also inhibited attachment of chondrocytes to fibronectin and disrupted assembly of actin filaments. These effects of SNO‐GSH and cytokine‐induced NO production were reversed in the presence of hemoglobin and the NO synthase inhibitor N G ‐monomethyl arginine, respectively. Conclusion . NO interferes with chondrocyte migration and attachment to fibronectin, an extracellular matrix protein, probably via effects on the actin cytoskeleton. These effects of NO may result in impairment of cartilage repair, by interfering with the extracellular matrix regulation of chondrocyte function.